2014
DOI: 10.1055/s-0034-1375570
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumors of the Spine

Abstract: ).Spinal tumors consist of a large spectrum of various histologic entities. Primary spinal tumors may arise from the spinal cord (intraaxial or intramedullary space), the surrounding leptomeninges (intradural extramedullary space), or the extradural soft tissues and bony structures (extradural space). Almost 60% of the spinal tumors are located in the extradural space, whereas 40% are located within the dural sac. Primary tumors of the spine are uncommon and represent < 5% of all bone neoplasms as compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 37 publications
(50 reference statements)
4
33
1
Order By: Relevance
“…We also found that there was a 3:2 predilection of males to females in EWS, which has been previously supported in smaller studies of EWS [12]. No gender predilection was found, however, in our cohort of OGS patients, despite previous literature with smaller case series citing a male predilection [23]. In terms of survival outcomes, patients with spinal OGS had a dismal overall median survival of 1.3 years, and a 5-year OS and DSS of 18% and 27%, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also found that there was a 3:2 predilection of males to females in EWS, which has been previously supported in smaller studies of EWS [12]. No gender predilection was found, however, in our cohort of OGS patients, despite previous literature with smaller case series citing a male predilection [23]. In terms of survival outcomes, patients with spinal OGS had a dismal overall median survival of 1.3 years, and a 5-year OS and DSS of 18% and 27%, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…This association stands to reason when considering that both these malignancies are classically known to be aggressive malignancies with significant soft tissue extension, particularly in the spine [23,27]. Notably, tumor size was found to be an independent survival determinant in patients with OGS, a finding that is consistent with prior cohort studies with smaller patient pools [17].…”
Section: Discussionsupporting
confidence: 75%
“…Chordomas show signal characteristics parallel to nucleus pulposus of the disk (notochord) on MR being low to intermediate signal on T1-WI (Figure 5a) and very high signal on T2-WI [19]. Coronal images on MRI demonstrate a “mushroom” appearance of the tumor (Figure 5c).…”
Section: Chordomamentioning
confidence: 99%
“…The most common location is the sacrococcygeal region, followed by the lumbar and the thoracic spine. Cervical spine involvement is rare (3.2% of patients) [19]. In the nonsacral spine, most lesions (60%) originate in the posterior elements with extension into the vertebral body [1].…”
Section: Ewing Sarcoma and Pnetmentioning
confidence: 99%
“…It constitutes approximately 20% of all bone tumors in China2. GCT of the spine (SGCT) are uncommon, accounting for approximately 2%–15% of all bone GCT and approximately 16.2% of all primary tumors of the spine3, 4, 5.…”
Section: Introductionmentioning
confidence: 99%